Penerapan Metode TGT (Teams-Games-Tournament) untuk Meningkatkan Kreativitas Anak Usia 5-6 Tahun di TK Negeri Pembina Kecamatan Janapria - Ema Nopiani; Gunawan Gunawan; Nurhasanah Nurhasanah (Indonesian Publication Center, 2022)
The TGT (Teams-Games-Tournament) learning method is a learning model that aims to enhance the development of children's creativity through learning carried out in groups to determine the extent of children's knowledge during learning. This type of research is experimental research with a pre-experimental designs approach (One-Group Pretest-Posttest Design) with a population of 25 children in group B, and a sample of 12 children in TK Negeri Pembina, Janapria District. The data collection tools used were observation and documentation, while the data analysis techniques used were descriptive analysis and inferential analysis (normality test and t-test). The results showed that the initial test obtained an average value (mean) of 25.58%, while the final test obtained an average value (mean) of 55.42%. In the data normality test, the initial test value (0.107> 0.05) means that the resulting data is normally distributed and in the final test (0.200> 0.05) it means that the resulting data is normally distributed. Whereas in the t-test the value of sig. (2-tailed) of 0.000 <0.05 which means that it can be concluded that H1 is accepted and H0 is rejected, meaning that the application of the TGT (Teams-Games-Tournament) learning method influences the development of children's creativity in Pembina State Kindergarten, Janapria District. There is a significant difference between the average value before treatment (pre-test) and the average value after treatment (post-test). The results of this study indicate that the average score on the test increases, so it can be concluded that the application of the TGT method can increase the creativity of children aged 5-6 years.